Effect of Oxide Presence in Activated Carbon on Arsenic Removal: 10.32526/ennrj/21/20230066 - Vong, Thearak; Phat, Korea; Lee, Seunghee; Kang, Shinhoo; Oh, Jinhwan (Environment and Natural Resources Journal, 2023)
This study investigated the effect of oxides on the removal of As when present in simple mixtures with granular activated carbon (GAC) particles. The performance of these mixtures was compared with other reported GAC-based adsorbents. A standard curve for ultraviolet adsorption vs. As concentration was obtained using the silver diethyldithiocarbamate (SDDC) method to evaluate various samples. A preliminary study was carried out to find the optimal conditions for experiments. For 50 mL samples with 2.35 ppm As, the optimal values of pH, adsorption time, and amount of adsorbent were pH 7, 30 min, and 50 mg, respectively. The ratio between the amount of adsorbent and well water in this study showed a superior As adsorption capacity (1 g/L, 2.1 mg/g) compared to similar adsorbents reported previously (12.5 g/L, 1.0-1.4 mg/g). Among the adsorbents, KOH-treated AC-Mn3O4 exhibited the best performance in As removal with an efficiency of 95%. The oxide particles had a synergistic effect with GAC on As removal. This was primarily due to the change in the potential of partially agglomerated nano Mn3O4 particles on the ACK surface. The influence of the surface area of the adsorbents was not pronounced. All results were explained in terms of microstructure, specific surface area, and zeta potential. This finding could be extended to other activated carbons (AC) obtained from different sources.